Labour administration services in the Caribbean : a guide - Goolsarran, Samuel J. (ILO Caribbean Office Port of SpainTT)
Gives an overview of the key elements in labour administration and industrial relations. Focuses on tasks to be performed: capacity building; conflict management; dispute settlement machinery; and, management issues in labour administration with particular reference to international labour standards impacting on the labour portfolio.